Kondisi Kebersihan Lingkungan Berhubungan dengan Risiko Penularan Kasus Leptospirosis di Area Pasar Tradisional - Dyah Widiastuti; Dwi Priyanto (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2020)
Leptospirosis is associated with occupations which exposed workers to contaminated environments. The risk of leptospirosis exposure in the market as a gathering place for many people needs to be assessed, to obtain the basis for decision making to anticipate leptospirosis transmission. This study aimed to determine the relationship between market environmental conditions including market sanitation conditions, the level of rat density and the presence of leptospira-positive rats toward the history of leptospirosis exposure among market workers (traders and janitors). A cross sectional study conducted in 35 markets in Banjarnegara and 175 market workers randomly selected. Blood samples analysed using ELISA against 40 Kda pathogenic Leptospira protein. Rat trapping conducted in each market for two days with 100 traps. The caught mice examined with Polymerase Chain Reaction (PCR) to detect the presence of Leptospira bacteria in their kidneys. Leptospirosis exposure was spread in 17 markets in Banjarnegara. The PCR examination showed that the pathogenic Leptospira infected rats were spread in four markets in Banjarnegara. Chi square test showed that the hygene condition in market area was significantly associated with the leptospirosis exposure. Markets workers (traders and janitors) were at risk for leptospirosis proved by high seroprevalence of leptospirosis in this study.